Sustainable transport of goods using combined transport solutions: The case of EU - Marek Minárik (Naše gospodarstvo / Our Economy, 2021)
This paper analyzes the importance of bimodal solutions in the rail-road transport of goods with an emphasis on the aspect of ecology within the geographical region of EU-28. Using the panel regression analysis in the period from 2010 to 2019, we are trying to confirm the dependence between the road and rail transport of goods by applying several freight units' measures: the freight transport performance in tonne-kilometres, the freight transport performance in tonne-kilometres per thousand of USD, and the amount of goods transported in thousands of tonnes. The application of data to all selected freight units' measures in the regression models confirms a relationship between road and rail transport. A direct relationship between these two modes of transport confirms the complementarity effect, which means that, in most cases, the goods transport solutions require the combination of road and rail mode, where the railway should be considered as the main transport/carrier, the road transport, however, should have the role of short pre-transport or post-transport. The ecological aspect of such bimodal solutions can also be emphasized since the railway transport is considered as an ecological mode.
Keywords: M21; R40; Q56; 330; bimodality; combined transport of goods; ecology; European Union